Percy Yarnold interviewed by John Meredith for the John Meredith folklore collection - Yarnold, Percy, 1907 -; Meredith, John, 1920-2001. (1985)
Folkloric recording. Percy Yarnold plays concertina. Yarnold speaks of the context of each song and acknowledges his sources; his memories of learning and playing concertina and accordion; his memories and experiences playing at dances, local players; his uncle and friend Keightley; the instruments he plays.
Percy Yarnold plays Anglo/German concertina. Concertina: 1. Keightley's Scottische (played twice) -- Concertina: 2. Uncle Willies set tunes -- 3. Alf Lyndon's scottische (throwing his feathers away) played twice -- Concertina: 4. Two Keightly waltzes.
Recorded on 21 January 1985 at Wingham.
Also available online
Keywords: Yarnold, Percy, -- 1907- -- Interviews; Concertina music; Folk dance music -- Australia